Daphnopsis flavicarpa, a new species of Thymelaeaceae from the Brazilian Atlantic Forest - Goulart, Gustavo; Amorim, André M.; Rossi, Lúcia; Fiaschi, Pedro (Phytotaxa, 2026)
A new species of Daphnopsis subg. Daphnopsis (Thymelaeaceae) from the Atlantic Forest of Bahia, Espírito Santo, and Minas Gerais states in Brazil, is here described. This new taxon is morphologically related to other Brazilian species of this subgenus, such as D. brasiliensis and D. pseudosalix, differing from these two by having flowers with an elongate hypanthium, 6–8 mm long (vs. 1.5–2.5 mm long), and yellow to orange mature drupes (vs. white). A detailed morphological description with taxonomic, habitat, and phenology notes is presented. Moreover, we provide a photographic plate, geographic distribution map, and an identification key to Brazilian species of D. subg. Daphnopsis.